Embedding an object : while tracing memories - Helen Svava Helgadóttir 1983- (2021)
In this thesis I give an account of my artistic practice. I describe and analyze older artworks of mine dating back to 2014 ending with an in depth reflection and analysis of my latest exhibition Eyelid, exhibited in March 2021. These works I have chosen to include I feel embody my methods and approach towards making an art object. I talk about how important the ideas of embodiment and embedding became to my whole process, how increasingly I came to realize that my personal experience and approach based on intuition and narrative are of equal importance to the arguments made from others and my surrounding environment. In the same way the object and its materiality is as important as its placement in the space it is located in. Embodied Critical Thinking, as a description and a method, is always about moving from one point of view to another Looking at the process of making these works I have been tracing back from traveling the wilderness of the African tundra to being at home during pandemic times feeling stuck within the fragile and lucid boundaries of my own skin. I see my works as a venue for sorting through my personal narratives and experiences, through the senses and via dialogue from others and the surrounding environment. It is a space where I can research vulnerability and shame, desire and regret, belonging and meaning and so forth. It is a venue where I can keep participating in these new ways of creating and understanding.